4, 5-Dihydro-1H-pyrazole: an indispensable scaffold. (June 2014) - Alex, Jimi Marin; Kumar, Raj
Abstract Pyrazoles, categorized as nitrogen-containing heterocycles, are well known for their interminable participation in the field of perpetual research and development of therapeutical active agents. As a consequence pyrazoles became an inevitable core of numerous drugs having diverse activities. The broad spectrum of activities portrayed by the pyrazoles instigated the researchers to modify the pyrazole ring as 4, 5-dihydro-1H-pyrazoles commonly known as 2-pyrazolines. The present review is a concerted effort to retrace compounds covered from 2009-till date which owe diverse biological activities to the 2-pyrazoline scaffold and also condenses the retro-synthetic approaches employed for their synthesis. This endeavor culminated in revelation that inhibitory potential varied when the substituents in particular N-substituents of 2-pyrazolines were altered.